Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How can I show $$\log(1+\frac{X}{A})\log(1+\frac{Y}{B})\ge \log(1+\frac{X}{B})\log(1+\frac{Y}{A})$$ if $X\ge Y>0$ and $A\ge B>0$?

share|improve this question
    
17 views and no comment yet! Any hint? Is it too simple or too hard? –  Mohsen Jun 8 '11 at 23:26
1  
too many variables... where does the problem origin from? –  plusepsilon.de Jun 8 '11 at 23:42
4  
You can fix $ A \ge B > 0 $ and define the function $ f(u) = \ln (1+u/A) / \ln (1+u/B) $. If you prove $ f'(u) > 0 $ for all $ u > 0 $, you'll have demonstrated it is monotonic increasing and therefore $ X \ge Y > 0 \implies f(X) \ge f(Y) $ which entails your inequality up there. –  anon Jun 8 '11 at 23:47
    
@user11848: It's related to the speed of computer networks :) Not an assignment, that's my research. –  Mohsen Jun 8 '11 at 23:54
    
@anon: Thanks. It really works. –  Mohsen Jun 9 '11 at 0:12
add comment

1 Answer

up vote 3 down vote accepted

Given $\alpha \geq 1$, define $f_\alpha(u) = \frac{\log(1+\alpha u)}{\log(1+u)}$ for $u>0.$

Show that $f_\alpha$ is an non-increasing.

Then if $\alpha = X/Y$, let $u=Y/A$ and $u'=Y/B$. So $u\leq u'$, and, since $f_\alpha$ is non-increasing, $f_\alpha(u)\geq f_\alpha(u')$. Expand that out, you get:

$$\frac{\log(1+X/A)}{\log(1+Y/A)} \geq \frac{\log(1+X/B)}{\log(1+Y/B)}$$

which is equivalent to the result you want.

So you only need to show that $f_\alpha$ is non-increasing, or, alternatively, that $f_\alpha'(u)\leq 0$ for all u>0.

But:

$$f_\alpha'(u) = \frac{\alpha(1+u)\log(1+u) - (1+\alpha u)\log(1+\alpha u)}{(1+u)(1+\alpha u)\log^2(1+u)}$$

So you need to show that $\alpha(1+u)\log(1+u) \leq (1+\alpha u)\log(1+\alpha u)$ when $\alpha\geq 1$ and $u > 0$.

This can be thought of as saying that $$g_u(z)=\frac{(1+uz)\log(1+uz)}{z}$$ has the property that $g_u(1)\leq g_u(\alpha)$ when $\alpha\geq 1$.

Now we show that $g_u$ is non-decreasing.

$$g_u'(z) = -\frac{(1+uz)\log(1+uz)}{z^2} + \frac{u\log(1+uz) + u}{z}$$

which simplifies to:

$$\frac{uz-\log(1+uz)}{z^2}$$

But $w\geq\log(1+w)$ for all $w\geq 0$. Setting $w=uz$, we see that $g_u'(z)$ is non-negative when $z>0$, and thus, in particular, $g_u(1)\leq g_u(\alpha)$ when $\alpha\geq 1$ and $u>0$. So $f_u'$ is non-positive, so $f_u$ is non-increasing, and we are done.

share|improve this answer
    
Thank you very much. I think your answer is quite similar to anon's comment above. But I think his approach is a simpler one. Anyways, your answer is perfect. –  Mohsen Jun 9 '11 at 1:16
    
I was verifying your answer today and I found there is a problem with it. Actually, I think the numerator must be $\alpha (1+u)\log(1+u) - (1+\alpha u)\log(1+\alpha u)$ instead of the one you wrote (i.e. the first term has an $\alpha$ multiplier). I believe the general idea of your proof still holds but it needs a bit modification. I'll get back if I found the answer. But write here if you have any idea. –  Mohsen Jun 20 '11 at 21:43
    
@Mohsen You are right, I'll see what I can do to fix that. –  Thomas Andrews Jun 22 '11 at 15:01
    
It's perfect. Thank you. –  Mohsen Jun 22 '11 at 19:27
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.